Social Infrastructure and Halal Tourism Village: A Study on Communities Around Lon Malang Beach, Madura - Bawono, Yudho; Wahyuni, Hera (E-Journal of Tourism; Volume 12 Number 1 (March 2025)DO - 10.24922/eot.v12i1.124078, 2025)
By optimizing social infrastructure, it is expected that changes will occur in the community. The aim of this research is to provide an important input regarding tourism development, especially halal tourism villages in Sampang Regency through optimizing social infrastructure in the community around Lon Malang Beach, Sampang Regency. One of the expected changes is the development of Bira Tengah Village as a halal tourism village. This research was conducted in Bira Tengah Village, Sokobanah District, Sampang Regency. The research employed a qualitative case study method. The research participants (IM, N, and MA) were selected according to the following criteria: 1) Residents of Bira Tengah Village; 2) Employed as tourism actors for at least one year. Participants were selected using purposive and snowball sampling methods. The data were collected through observations and interviews. The data then were analyzed by using the Miles & Huberman interactive model, starting with data collection, data reduction, data display, and conclusion drawing/verifying. The validity of the data was assessed by testing its credibility, transferability, dependability, and confirmability. This research found 3 themes, including: (a) The beginning of Lon Malang Beach; (b) Suboptimal social infrastructure; and (c) Limited knowledge about halal tourism villages. Suggestions for tourism stakeholders at Lon Malang Beach, including the Sampang Regency Government and the Sampang Regency Culture and Tourism Office, are expected to promote the development of halal tourism in Bira Tengah Village, Sokobanah District, Sampang Regency.